2021
DOI: 10.1038/s41598-021-88614-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineered adeno-associated virus 3 vector with reduced reactivity to serum antibodies

Abstract: The natural serotypes of adeno-associated virus (AAV) or their variants, such as AAV8 and AAV5, are commonly used as vectors in the clinical programs for liver-targeted gene therapy. While AAV8 vectors are not highly efficient at targeting primary human hepatocytes, AAV3 vectors have recently demonstrated remarkable efficiency at targeting both human and non-human primate hepatocytes. However, the presence of high levels of neutralizing antibodies (NAbs) impedes transduction into hepatocytes, representing a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…A recent report showed that the CRISPR system was successfully delivered into human hepatocytes from humanized liver chimeric mice using genetically modified AAV, [ 17 ] which could be a potential HBV‐CRISPR delivery option in patients. In particular, a genetically modified AAV vector (AAV.GT5) has been reported to have high transduction efficiency in human hepatocytes and low reactivity with neutralizing antibodies, [ 10 ] which would enable repeated administration to deliver CRISPR into all HBV‐infected hepatocytes in the liver. A potential concern about CRISPR treatment is that it may induce DSBs of the HBV DNA integrated in the host genome and cause genome instability and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report showed that the CRISPR system was successfully delivered into human hepatocytes from humanized liver chimeric mice using genetically modified AAV, [ 17 ] which could be a potential HBV‐CRISPR delivery option in patients. In particular, a genetically modified AAV vector (AAV.GT5) has been reported to have high transduction efficiency in human hepatocytes and low reactivity with neutralizing antibodies, [ 10 ] which would enable repeated administration to deliver CRISPR into all HBV‐infected hepatocytes in the liver. A potential concern about CRISPR treatment is that it may induce DSBs of the HBV DNA integrated in the host genome and cause genome instability and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Thus, it is difficult to eradicate cccDNA from infected hepatocytes with currently available antiviral therapies. Several potential new therapies, including capsid assembly modulators, [ 7 , 8 , 9 , 10 ] nucleic acid–based polymers, and antisense oligonucleotides tested in clinical trials, also do not directly target cccDNA. Therefore, further development of therapeutics targeting cccDNA is awaited.…”
Section: Introductionmentioning
confidence: 99%
“…AAV5 and AAV8, which have been widely used in gene therapy with the liver as the target in clinical trials, and AAV3B, which reportedly possesses a high gene transfer efficiency to the human liver. 12,20,21…”
Section: Comparison Of the Capsid Amino Acid Sequence Among Aav Serot...mentioning
confidence: 99%
“…4 AAV.GT5 showed robust transgene expression in human primary hepatocytes as well as Huh-7 and HepG2 (Supplemental figure S2), as reported previously. 16 Transduction efficiency of human primary hepatocytes with AAV.GT5 was more than 100 times higher than AAV-Spark100 and AAV5 (Supplemental figure S2). Conversely, AAV-Spark100 showed the most efficient transduction in murine hepatocyte cell line TLR3 (Supplemental figure S2).…”
Section: Efficient Transgene Expression In Human Hepatocytes By Aavgt...mentioning
confidence: 99%